2009
DOI: 10.2223/jped.1886
|View full text |Cite
|
Sign up to set email alerts
|

Peak pressure and tidal volume are affected by how the neonatal self-inflating bag is handled

Abstract: Objective: To evaluate how different ways of handling the neonatal self-inflating bag influence peak pressure and tidal volume.Methods: This is an experimental study involving 141 different professionals (physicians, resident physicians, physiotherapists, nurses, and nursing technicians), who ventilated an artificial lung, adjusted to simulate the lung of a term neonate, using a self-inflating bag. Each professional handled the ventilator in five different ways: a) using both hands (10 fingers); and, with only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 20 publications
(21 reference statements)
0
20
0
5
Order By: Relevance
“…However, most of these studies were directed to adult patients, 4,[6][7][8][9] and only a few of them addressed this aspect in newborns. 11,24 Ganga-Zandzou et al 24 and Bassani et al 11 demonstrated that delivered peak pressures are higher when more fingers are used to compress the bag. Bassani et al 11 observed that this relationship also occurs for V T , as shown in earlier studies that compared the use of 1 or 2 hands to simulate ventilation in adults.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, most of these studies were directed to adult patients, 4,[6][7][8][9] and only a few of them addressed this aspect in newborns. 11,24 Ganga-Zandzou et al 24 and Bassani et al 11 demonstrated that delivered peak pressures are higher when more fingers are used to compress the bag. Bassani et al 11 observed that this relationship also occurs for V T , as shown in earlier studies that compared the use of 1 or 2 hands to simulate ventilation in adults.…”
Section: Discussionmentioning
confidence: 99%
“…11,24 Ganga-Zandzou et al 24 and Bassani et al 11 demonstrated that delivered peak pressures are higher when more fingers are used to compress the bag. Bassani et al 11 observed that this relationship also occurs for V T , as shown in earlier studies that compared the use of 1 or 2 hands to simulate ventilation in adults. 4,[6][7][8][9] These observations are confirmed in the present study with a larger volunteer sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations